Assessing students' values and costs in three countries: Gender and age differences within countries and structural differences across countries - Gaspard, Hanna; Jiang, Yi; Piesch, Heide; Nagengast, Benjamin; Jia, Ning; Lee, Jeesoo; Bong, Mimi (Learning and individual differences, 2020)
Drawing upon expectancy-value theory (Eccles et al., 1983), we aimed to test the cross-cultural validity of scales for assessing adolescent students' values and costs in Germany, China, and Korea with a focus on gender and age differences and the potential cross-cultural generalizability of the structural relations. In each country (N = 483 in Germany, N = 598 in China, and N = 617 in Korea), we assessed students' self-efficacy, values, and costs in math and English using the same questionnaires. Within each country, the scales showed evidence of strong measurement invariance across both gender and age, and there were gender and age differences in the mean levels of values and costs. Weak measurement invariance was shown across countries. The structural relations among self-efficacy, values, and costs were very similar across the two academic subjects within each country, whereas there were slight differences between countries. •We assessed students' values and costs in math and English in three countries.•The scales showed strong measurement invariance across age and gender within each country.•There were gender and age differences in values and costs within each country.•The scales showed weak measurement invariance across countries.•Correlations among self-efficacy, values and costs showed differences across countries.